The survival and reproductive performance of Daphniopsis australis (Cladocera: Daphniidae) in response to temperature changes / Hasnun Nita Ismail, Jian Guang Qin and Laurent Seuront - Ismail, Hasnun Nita; Jian, Guang Qin; Seuront, Laurent (Universiti Teknologi MARA, Perlis, 2011)
The thermal tolerances and reproduction of Daphniopsis australis were investigated using a single clone under laboratory conditions. Based on survivorship, measurements of thermal tolerance were conducted using acute exposure within 24, 48 and 72 hours. The upper limit of tolerance was at 28°C, but animals successfully survived until the lowest temperature (4°C) regardless of exposure times. A minimum temperature increment of 6°C above the control temperature (22°C) was detrimental to survival while the optimal temperature of this species was detected from 4 to 26°C. Variation in pattern of reproduction was observed in the range of temperature from 16 to 25°C. The reproductive parameters including age at first reproduction (AFR), clutch number, egg development time (EDT) and total offspring production were significantly affected by temperature changes. Low and high temperature significantly delayed the age for first reproduction and reduced the clutch number. However, EDT and total offspring were negatively related with an increase in temperature. An extreme thermal condition was detected at 25°C where reproductive outputs were adversely affected. Our results suggest that D. australis is a eurythermal species, but a rapid increase of temperature could threaten its survival. Reproduction of this species is favourable in the narrow range of temperature with the most optimal temperature is likely at 20°C. This study contributes to the understanding of the impact of global warming on the sustainability of zooplankton fauna in arid temperate regions.